Social discourse in a globalised era: Towards the concept of development matrix - Sharma, Subhash (1998)
The author argues for adoption of a development matrix as the basis for social discourse in a globalised era for a better understanding of the role of State. Conceptualising development matrix through an analysis of human activities in terms of their market and non-market contexts and modes of organisation in terms of corporate and non-corporate structures, the author presents his Vishwa model and the idea of Vishwanisation as a new construct to meet challenges of globalisation. Admitting critically of cultural setting and its diversity in a holistic developmental view of a society, he conceptualises Indian society as a matrix society, and suggests a paradigm shift from dialectical analysis of a society towards a matrix analysis. He also proposes the idea of dialectical intensity as a basis to understand complexity of a matrix society. - Reproduced
Keywords: Public administration; Globalization; Development indicators